Hybrid Search Approach for Retrieving Medical and Health Science Knowledge from Quran - Afifi Mohamad Safee, Muhammad; Mohd Saudi, Madihah; A. Pitchay, Sakinah; Ridzuan, Farida; Basir, Nurlida; Saadan, Kamarudin; Nabila, Fatin (International Journal of Engineering and Technology, 2018)
Keyword-based technique has low accuracy and always leads to wrong information retrieved. Therefore, many researchers implement semantic search to overcome the above problems. Many researchers have built different Quran ontology in various domains to facilitate the knowledge representation in the Quran. Nevertheless, there are many domain concepts mentioned in the Quran which are not yet covered, especially for the Medical and Health Science domain. Hence, this research presents the development of ontology for the Medical and Health Science domain in the Quran and implementation of ontology-based search method to answer related queries in the Quran. The development of ontology adopts the ontology 101 approach which later evaluated by Quran experts. Furthermore, a hybrid search tool was developed that encompassed semantic-based and keyword based technique to answer a user query. The search tool was evaluated using the Recall and Precision measurements, which shows high accuracy in retrieving the Medical and Health Science knowledge in the Quran. For future work, this research can be used as a reference and basis to answer user queries, data integration with other applications or existing ontology can be further expanded.Â Â